The change of retinal microvascular in APAC eyes and fellow PACS eyes detected using wide-field swept-source optical coherence tomographic angiography - Zhao, Rumin; Geng, Wenhui; Zhang, Zijian; Wu, Yunlong; Wang, Xiaotong; Zhao, Bojun (Frontiers in Medicine, 2025)
PurposeThis study aimed to quantitatively evaluate changes in vascular parameters in a 12 mm × 12 mm region centered on the fovea with wide-field swept-source optical coherence tomographic angiography (WF SS-OCTA), and establish their correlations with structural parameters in acute primary angle closure (APAC) eyes, as well as in fellow primary angle-closure suspect (PACS) eyes.MethodsIn this retrospective study, WF SS-OCTA was utilized to measure vascular parameters in a 12 mm × 12 mm region centered on the fovea in 31 patients (31 APAC eyes and 31 fellow PACS eyes). Vascular parameters included vessel density (VD) of the superficial vascular complex (SVC) and deep vascular complex (DVC). Structural parameters comprised macular ganglion cell complex (GCC) thickness and peripapillary retinal nerve fiber layer (pRNFL) thickness. Pre- and postoperative (3 month after APAC attack) differences between APAC and PACS eyes were statistically analyzed.ResultsNo significant differences were observed in vascular density or structural parameters in PACS eyes pre- and postoperatively (p > 0.05). In APAC eyes, postoperative SVC VD showed no significant change in the 0–6 mm region but decreased significantly in the 6–12 mm annular region centered on the fovea (p < 0.05). DVC VD increased across all scanned regions postoperatively (p < 0.05). The average pRNFL thickness, quadrant-specific pRNFL thickness, and GCC thickness were significantly reduced after operation (p < 0.05). Multivariate linear regression revealed positive correlations between GCC thickness, SVC VD (0–6 mm, 0–12 mm, 6–12 mm), and pRNFL thickness (p < 0.001).ConclusionWide-field SS-OCTA revealed spatially distinct vascular responses in APAC eyes: underlying axonal loss with concomitant SVC compromise in the 6–12 mm annular region centered on the fovea and partial DVC recovery at 3 months after APAC attack, highlighting WF SS-OCTA’s utility in monitoring APAC progression.